The Impact of Tax Compliance on State Revenue: A Systematic Analysis Based on Recent Literature - Nofitasari, Susi; Tomy, Chairian (Universitas Indonesia Mandiri, 2025)
This study examined the factors influencing tax compliance in Indonesia, with a particular focus on tax education, technological advancements, and policy reforms. The research employs a qualitative approach, which includes an extensive literature review and policy analysis. The findings reveal that tax literacy, digital tax systems, and perceptions of tax policy fairness play a significant role in determining compliance levels. The study also identifies challenges in reaching Small and Medium Enterprises (SMEs) and underserved regions, suggesting that while short-term measures such as tax amnesty programs may provide temporary relief, they do not lead to sustainable improvements. Recommendations to enhance tax compliance include improving tax education, expanding digital tax solutions, and ensuring transparency in policy implementation. The contribution of this study lies in providing a comprehensive understanding of the interconnections between education, technology, and policy in shaping tax compliance and offering actionable recommendations for policymakers to establish long-term solutions.